Magnetic Resonance Imaging of Single Co-Labeled Mesenchymal Stromal Cells after Intracardial Injection in Mice - Salamon, J.; Wicklein, D.; Didié, M.; Lange, C.; Schumacher, U.; Adam, G.; Peldschus, K. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: The aim of this study was to establish co-labeling of mesenchymal stromal cells (MSC) for the detection of single MSC in-vivo by MRI and histological validation.Materials and Methods: Mouse MSC were co-labeled with fluorescent iron oxide micro-particles and carboxyfluorescein succinimidyl ester (CFSE). The cellular iron content was determined by atomic absorption spectrometry. Cell proliferation and expression of characteristic surface markers were determined by flow cytometry. The chondrogenic differentiation capacity was assessed. Different amounts of cells (n1 = 5000, n2 = 15 000, n3 = 50 000) were injected into the left heart ventricle of 12 mice. The animals underwent sequential MRI on a clinical 3.0 T scanner (Intera, Philips Medical Systems, Best, The Netherlands). For histological validation cryosections were examined by fluorescent microscopy.Results: Magnetic and fluorescent labeling of MSC was established (mean cellular iron content 23.6 ± 3 pg). Flow cytometry showed similar cell proliferation and receptor expression of labeled and unlabeled MSC. Chondrogenic differentiation of labeled MSC was verified. After cell injection MRI revealed multiple signal voids in the brain and fewer signal voids in the kidneys. In the brain, an average of 4.6 ± 1.2 (n1), 9.0 ± 3.6 (n2) and 25.0 ± 1.0 (n3) signal voids were detected per MRI slice. An average of 8.7 ± 3.1 (n1), 22.0 ± 6.1 (n2) and 89.8 ± 6.5 (n3) labeled cells per corresponding stack of adjacent cryosections could be detected in the brain. Statistical correlation of the numbers of MRI signal voids in the brain and single MSC found by histology revealed a correlation coefficient of r = 0.91.Conclusion: The study demonstrates efficient magnetic and fluorescent co-labeling of MSC and their detection on a single cell level in mice by in-vivo MRI and histology. The described techniques may broaden the methods for in-vivo tracking of MSC.Key Points:• Detection of single magnetically labeled MSC in-vivo using a clinical 3.0 T MRI is possible.• Fluorescent and magnetic co-labeling does not affect cell vitality.• The number of cells detected by MRI and histology has a high correlation.Citation Format:• Salamon J, Wicklein D, Didié M et al. Magnetic Resonance Imaging of Single Co-Labeled Mesenchymal Stromal Cells after Intracardial Injection in Mice. Fortschr Röntgenstr 2014; 186: 367 – 376
Keywords: magnetic resonance imaging; mesenchymal stromal cells; SPIO; intracardial injection